Utilizing Social Media to Combat Sexual Violence: A Study of the Speak Up Movement on Instagram - Sulastri, Rini; Walidah, Marsha Qolby; Sidik, Mohamad Dindin Hamam (Universitas Islam Negeri Sunan Gunung Djati Bandung, 2024)
This study aims to uncover the motivations and reasons behind victims' decisions to speak out on Instagram and evaluate the impact and responses to the speak-up movement against sexual violence. The research employs a qualitative method with data collection techniques including online observation, specifically through the social media platform Instagram, focusing on sexual violence survivors who courageously share their cases on this platform. The findings indicate that the speak-up movement on social media plays a crucial role in empowering victims, raising public awareness, and accelerating the enactment of the Sexual Violence Crime Law (UU TPKS). However, the study also identifies shortcomings in the responsiveness of authorities to the disclosed cases. The contribution of this research lies in providing new insights into Instagram's role in legal and social advocacy, as well as in the online observation methodology used to assess the impact of the speak-up movement and the direct experiences of survivors.